Programa "Leo más para leer mejor", basado en el enfoque interactivo y la formación de lectores autónomos en niños del quinto y sexto grado del nivel primaria, 2016 - López Rodríguez, Lita Nora (2019)
ABSTRACT The purpose of this research work was to determine the formation of autonomous readers in fifth and sixth grade children at the primary level through the "I read more to read better" program, based on the interactive approach to reading. The population was integrated by 120 students of fifth and sixth grade of primary level of the private educational institution "Santa Rita de Jesus" of the district El Porvenir in 2016. The pre-experimental design was used, with a single group. The test was applied to determine the level of training of autonomous readers. The program "I read more to read better" is based on the interactive approach of Isabel Solé's reading. Finally, it was found that the program "I read more to read better" significantly improved the level of training of autonomous readers in children of fifth and sixth grade of the primary level.